2017
DOI: 10.26529/cepsj.173
|View full text |Cite
|
Sign up to set email alerts
|

The Teacher as One of the Factors Influencing Students’ Perception of Biology as a School Subject

Abstract: The main aim of our research was to determine whether the teacher is one of the factors influencing students’ perception of biology as a school subject. The study also aimed to identify the influence of certain other factors in this regard, specifically: students’ gender and place of residence, the number of biology teachers who have taught the students, and theteachers’ gender. The sample consisted of 261 lower secondary school students (ISCED 2) in Slovakia, aged 14 and 15 years. A questionnaire with Likert-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…The study by Ainley & Ainley (2011) showed that relevance and personal meaning are important factors in students' appreciation, interest, and engagement with science content. Furthermore, when students are convinced of the potential benefits of the subject for their future careers, this translates into a positive attitude toward the subject (Kubiatko & al., 2017). Thus, it is important to note that teachers have a crucial role to play in developing students' affective connections and positive attitudes toward LES.…”
Section: Observations On the Perceived Preference For Les School Subjectmentioning
confidence: 99%
“…The study by Ainley & Ainley (2011) showed that relevance and personal meaning are important factors in students' appreciation, interest, and engagement with science content. Furthermore, when students are convinced of the potential benefits of the subject for their future careers, this translates into a positive attitude toward the subject (Kubiatko & al., 2017). Thus, it is important to note that teachers have a crucial role to play in developing students' affective connections and positive attitudes toward LES.…”
Section: Observations On the Perceived Preference For Les School Subjectmentioning
confidence: 99%
“…Beberapa siswa menganggap bahwa beberapa cabang biologi sebagai ilmu yang "tidak berguna" (Kubiatko et al, 2017) dan cenderung membosankan bagi siswa. Akibatnya, mereka tidak tertarik untuk belajar (Husamah et al, 2018).…”
Section: Pendahuluanunclassified
“…Biology is a broad field of knowledge that requires the acquisition of knowledge within and outside of classroom environments. On the other hand, it is a subject that is least preferred by high school students (Kubiatko et al, 2017). Furthermore, some topics in biology were found to be boring for students, such as systems, tissues, and power transformation (Derman, 2017).…”
Section: Introductionmentioning
confidence: 99%